FREQUENCY OF SENSORY DEFICIT IN TERMS OF TWO POINT DISCRIMINATION IN SPLIT THICKNESS SKIN GRAFTS AND LOCAL FLAPS FOR SOFT TISSUE DEFECTS OF FINGERS - Cheema, Saeed Ashraf; Ahmad, Awais (Journal of Ayub Medical College Abbottabad, 2012)
Background: The minimum distance between two stimulus points on the skin, which are perceived as distinct points, is defined as two point discrimination (TPD). Among the two types of TPD, i.e., static and dynamic, static two-point discrimination (STPD) is commonly used to determine digital nerve integrity. Local flaps usually do well in maintaining sensibility of the covered area in terms of two-point discrimination in contrast to split thickness skin grafts (STSG). Aim was to determine the frequency of sensory deficit in terms of Two Point Discrimination (TPD) in Split Thickness Skin Grafts (STSG) and local flaps for soft tissue defects of fingers three months postoperatively. Methods: Thirty-five patients underwent local flap coverage and other thirty-five had split thickness skin grafting for soft tissue defects of fingers depending upon nature of defect. Patients were followed up at 2, 4, 8 and 12 weeks. TPD, measured at 3 months of follow-up, of 7 mm was considered normal (no sensory deficit) and TPD of 8mm or more was considered as sensory deficit. Results: The sensory deficit observed at the end of 12th week post operatively was 8.6% in the patients with local flap coverage (3 patients) and 45.7% with STSG (16 patients). Patients with no sensory deficit were 91.4% (32 patients) in the local flap coverage and 54.3% (19 patients) in the STSG at 12th week of follow up. The relative ratio (RR) of sensory deficit in local flaps and STSG was 5 (>2). Conclusions: Local flaps are better options in terms of TPD preservation as opposed to STSG for soft tissue defects of fingers. Keywords: Finger Injuries, Two Point Discrimination, Split Thickness Skin Grafting, Local flaps